Voltammetric studies of bidirectional catalytic electron transport in Escherichia coli succinate dehydrogenase: comparison with the enzyme from beef heart mitochondria. - Pershad, H; Hirst, J; Cochran, B; Ackrell, B; Armstrong, F (1999)
The succinate dehydrogenases (SDH: soluble, membrane-extrinsic subunits of succinate:quinone oxidoreductases) from Escherichia coli and beef heart mitochondria each adsorb at a pyrolytic graphite 'edge' electrode and catalyse the interconversion of succinate and fumarate according to the electrochemical potential that is applied. E. coli and beef heart mitochondrial SDH share only ca. 50% homology, yet the steady-state catalytic activities, when measured over a continuous potential range, display very similar catalytic operating potentials and energetic biases (the relative ability to catalyse succinate oxidation vs. fumarate reduction). Importantly, E. coli SDH also exhibits the interesting 'tunnel-diode' behaviour previously reported for the mitochondrial enzyme. Thus as the potential is lowered below ca. -60 mV (pH 7, 38 degrees C) the rate of catalytic fumarate reduction decreases abruptly despite an increase in driving force. Since the homology relates primarily to residues associated with active site regions, the marked similarity in the voltammetry reaffirms our previous conclusions that the tunnel-diode behaviour is a characteristic property of the enzyme active site. Thus, succinate dehydrogenase is an excellent fumarate reductase, but its activity in this direction is limited to a very specific range of potential.